3
$\begingroup$

The function $f : \mathbb{R} \rightarrow \mathbb{R}$ satisfies $f(x) f(y) - f(xy) = x + y$ for all $x$, $y \in \mathbb{R}$. Find $f(x)$.

$\endgroup$
11
$\begingroup$

With $y=1$, we can establish that $$ f(x)f(1)-f(x)=x+1\implies f(x)=\frac{x+1}{f(1)-1}\cdot\tag{$*$} $$ Note that the division by $f(1)-1$ is valid because $f(1)$ cannot be $1$ (if it were, $f(x)f(1)-f(x)$ would be identically $0$ whereas $x+1$ would vary with $x$.) It remains to find $f(1)$. First, $$ x=0,y=0\implies [f(0)]^2-f(0)=0\implies f(0)=0\text{ or }f(0)=1. $$ But $f(0)$ cannot be $0$, as we can see below: $$ x=1,y=0\implies f(1)f(0)-f(0)=1\implies f(0)=1, f(1)=2. $$ We conclude that $f(x)=x+1$.

$\endgroup$
  • 1
    $\begingroup$ It wasn't obvious to me at first why f(0) couldn't be 0. So I tried to apply it to the $f(x)=\frac{x+1}{f(1)-1} \text{ and got } f(0)=0=\frac{0+1}{f(1)-1} $ But 1 cannot be 0. Awesome answer @yurnero. P.S. Tried to up your answer again but found out it only takes away if you do it again :p $\endgroup$ – randomgirl Mar 7 '15 at 0:39
  • $\begingroup$ You can also just let $x=1$ and $y=1$ and solve the quadratic. No need for the funny reasoning about $f(0)$. $\endgroup$ – DanielV Mar 7 '15 at 1:48
  • $\begingroup$ @DanielV I thought about that but it wasn't clear to me how to eliminate $f(1)=-1$ without further substitution. $\endgroup$ – yurnero Mar 7 '15 at 2:42
1
$\begingroup$

Setting $y = 0$ gives $f[x] f[y] - f[x y] = f[0] (f[x] - 1)$ and also $f[x] f[y] - f[x y] = x$

$f[0] (f[x] - 1) == x$

Setting $x=0$ now gives

$f[0] (f[0] - 1) = 0$

If $f[0]$ is not zero, then $f[0] - 1$ must be zero.

So we have $f[0]=1$.

But then:

$f[x] - 1 = x$

and

$f[x] = x + 1$

$\endgroup$
  • 1
    $\begingroup$ Please see this tutorial on how to format mathematics on this site. $\endgroup$ – N. F. Taussig Mar 7 '15 at 1:24
  • $\begingroup$ Thank's. Try to do better next time. $\endgroup$ – Frieder Mar 7 '15 at 1:37
0
$\begingroup$

Setting $y = 0$, we get [f(0) f(x) - f(0) = x,] so $f(0) [f(x) - 1] = x$ for all $x$. In addition, setting $x = 0$, we get $f(0) [f(0) - 1] = 0$, so $f(0) = 0$ or $f(0) = 1$. But $f(0) [f(x) - 1] = x$ for all $x$, so $f(0)$ cannot be 0, which means $f(0) = 1$. Then $f(x) - 1 = x$, or $f(x) = \boxed{x + 1}$ for all $x$. It is easy to verify that this solution works.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.